“I Just Find It Easier to Let Go of Anger”: Reflections on the Ways in Which Yoga Influences How Young People Manage Their Emotions - Hagen, Ingunn; Skjelstad, Solbjørg; Nayar, Usha Sidana (Frontiers in Psychology, 2021)
In this article we discuss how young people experienced a school-based yoga intervention. We pay particular attention to how yoga provides a space for young people to deal with their emotions. We base our discussion on qualitative data from young people in Norway who participated in the European research project “Hippocampus: Promoting Mental Health and Well-being among Young People through Yoga”. The qualitative results are based on experiences described by these young people in individual semi-structured interviews and in diaries/logs. Our data include nine interviews performed in the spring of 2019 with young people in their late teens and early twenties, of Norwegian and refugee background. There were also 133 logs noted by the students exposed to the yoga intervention. In the qualitative interviews young people talk about yoga and emotional management, improved sleep habits and regulation. They also report improved ability to cope with and regulate stress. Yoga seemed especially beneficial for refugee trauma. In this article we have chosen to focus on young people’s utterances about emotions, as those were quite dominant in our data, especially in the interview material. We have identified instances of emotional regulation, but also of emotional processes and changes of emotions, all of which were related to these young students practicing yoga. The impact of yoga on emotions illustrates the potential of yoga to improve the well-being and mental health of young people.